Social Media Marketing’s Effectiveness on Purchase Intention Mediated by Brand Image and Trust - Huda, Fajar Nur Amri; Thoyib, Armanu; Hadiwidjojo, Djumilah (International Journal Labs, 2022)
Background: Marketing has created a potential industry in the fisheries sector. It has gotten within the realm of digital marketing, among others. Currently, social media is used for advertising fishery products online (Social media marketing). Aim: This study aims to ascertain how social media marketing initiatives affect brand image, consumer trust, and intention purchasing items. Method: Explanatory quantitative research is used in this study. The whole fishery e-commerce customer base that has followed fisheries' Instagram profiles makes up the population of this study. Due to rounding from 398, the samples for this study contained 398 respondents. The major data for this study came from the findings of the questionnaire distribution. The secondary data, however, was gathered through books, the internet, literature, and periodicals. Findings: To improve consumers' intention in purchasing products, businesses must focus on social media marketing initiatives, brand perception, and consumer confidence in Fisheries E-Commerce in Jakarta.